The identification and management of interstitial lung disease in systemic sclerosis: evidence-based European consensus statements. (February 2020) - Hoffmann-Vold, Anna-Maria; Maher, Toby M; Philpot, Edward E; Ashrafzadeh, Ali; Barake, Rafic; Barsotti, Simone; Bruni, Cosimo; Carducci, Paolo; Carreira, Patricia E; Castellví, Ivan; Del Galdo, Francesco; Distler, Jörg H W; et al.
Summary: Background: Systemic sclerosis-associated interstitial lung disease (ILD) carries a high mortality risk; expert guidance is required to aid early recognition and treatment. We aimed to develop the first expert consensus and define an algorithm for the identification and management of the condition through application of well established methods. Methods: Evidence-based consensus statements for systemic sclerosis-associated ILD management were established for six domains (ie, risk factors, screening, diagnosis and severity assessment, treatment initiation and options, disease progression, and treatment escalation) using a modified Delphi process based on a systematic literature analysis. A panel of 27 Europe-based pulmonologists, rheumatologists, and internists with expertise in systemic sclerosis-associated ILD participated in three rounds of online surveys, a face-to-face discussion, and a WebEx meeting, followed by two supplemental Delphi rounds, to establish consensus and define a management algorithm. Consensus was considered achieved if at least 80% of panellists indicated agreement or disagreement. Findings: Between July 1, 2018, and Aug 27, 2019, consensus agreement was reached for 52 primary statements and six supplemental statements across six domains of management, and an algorithm was defined for clinical practice use. The agreed statements most important for clinical use included: all patients with systemic sclerosis should be screened for systemic sclerosis-associated ILD using high-resolution CT; high-resolution CT is the primary tool for diagnosing ILD in systemic sclerosis; pulmonary function tests support screening and diagnosis; systemic sclerosis-associated ILD severity should be measured with more than one indicator; it is appropriate to treat all severe cases; no pharmacological treatment is an option for some patients; follow-up assessments enable identification of disease progression; progression pace, alongside disease severity, drives decisions to escalate treatment. Interpretation: Through a robust modified Delphi process developed by a diverse panel of experts, the first evidence-based consensus statements were established on guidance for the identification and medical management of systemic sclerosis-associated ILD. Funding: An unrestricted grant from Boehringer Ingelheim International.